1977
DOI: 10.1093/clinchem/23.12.2242
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automated vs. visual reading of urinalysis dipsticks.

Abstract: Semi-automated reflectance readings of urinalysis dipsticks showed better precision than visual readings in the case of artificially prepared urine samples containing glucose, ketone, and protein. Actual pathological specimens containing glucose, protein, and nitrite also showed that instrumental readings were better than visual. Results of repeated visual readings spread over three different color blocks for certain concentrations of glucose, ketone, and protein, whereas repeated instrumental readings were ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“… 12 18–20 Two studies have shown that automatic reading of urine test strips is more accurate than visual reading of the same test strip. 6 7 Peele et al already reported on this in 1977 using a semiautomated dipstick reader in a laboratory setting. However, technology has developed since and the described analyser is no longer available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 18–20 Two studies have shown that automatic reading of urine test strips is more accurate than visual reading of the same test strip. 6 7 Peele et al already reported on this in 1977 using a semiautomated dipstick reader in a laboratory setting. However, technology has developed since and the described analyser is no longer available.…”
Section: Discussionmentioning
confidence: 99%
“…However, technology has developed since and the described analyser is no longer available. 6 Tighe 7 performed his study in a laboratory setting, using aqueous spiked samples instead of patient samples, and although they did evaluate a POCT urine analyser, it was not compared with a laboratory reference standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests allow for the diagnosis of a variety of conditions and diseases including kidney disease, urinary tract infections, carbohydrate metabolism disorders, and liver disease [4,15,16]. For more sophisticated urinalysis tests, the dipsticks can be analyzed by a detector that analyzes the color of the test pads in order to improve the accuracy and precision of the tests [3,17]. Another common application for dipstick tests is for the analysis of water samples.…”
Section: Dipstick Devicesmentioning
confidence: 99%
“…Pen-based devices take advantage of flexible patterning, inexpensive costs, and small volumes, thereby saving time and increasing efficiency. 1 2 3 Pen-based techniques have been used to pattern surfaces for cell studies. 4 5 6 Such approaches can also be used to apply patterns on nano- or micro-scales for biological uses.…”
Section: Introductionmentioning
confidence: 99%